2019
DOI: 10.2196/14137
|View full text |Cite
|
Sign up to set email alerts
|

The Reach of the “Don’t Fry Day” Twitter Campaign: Content Analysis

Abstract: Background Skin cancer is the most common cancer in the United States, disproportionately affecting young women. Since many young adults use Twitter, it may be an effective channel to communicate skin cancer prevention information. Objective The study aimed to assess the reach of the National Council on Skin Cancer Prevention (NCSCP)’s 2018 Don’t Fry Day Twitter campaign, categorize the types of individuals or tweeters who engaged in the campaign, and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…The content analysis identified three themes: health-related expressiveness, health information, and health advice. Nguyen et al [34] developed a methodology that aimed to evaluate the influence of the campaign (Don't Fry Day) by the National Council on Skin Cancer Prevention (NCSCP)'s 2018 on Twitter, categorize types of accounts participating in the campaign, and determine the themes of the tweets. The dataset was collected from 1881 Twitter accounts.…”
Section: Social Media and Cancermentioning
confidence: 99%
“…The content analysis identified three themes: health-related expressiveness, health information, and health advice. Nguyen et al [34] developed a methodology that aimed to evaluate the influence of the campaign (Don't Fry Day) by the National Council on Skin Cancer Prevention (NCSCP)'s 2018 on Twitter, categorize types of accounts participating in the campaign, and determine the themes of the tweets. The dataset was collected from 1881 Twitter accounts.…”
Section: Social Media and Cancermentioning
confidence: 99%
“…Over the last five years, several groups have implemented Twitter awareness campaigns focused on breast cancer [ 10 ], skin cancer [ 11 ], mental health [ 12 ], cardio-oncology [ 13 ], HPV vaccination [ 14 ], and breastfeeding [ 15 , 16 ]. Independent of the varied content, audience, and duration across the studies, the methods used to assess campaigns were limited to one or several of the following approaches: content analysis of tweets; survey-based assessment of users’ knowledge; and/or quantitative analysis of Twitter Analytics metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Even though much effort has been put in primary prevention campaigns over the last decades (e.g., Doran et al, 2016;Nguyen et al, 2019;Stratigos et al, 2012), the regular engagement in sun protective behaviours is not yet widespread and sunburns are still prevalent. For example, three German studies found that 41% of the respondents had at least 1 sunburn in the previous year, that up to 17% of the respondents never use sunscreen, that only 30% of the respondents avoid sunbathing, and that only about half of the respondents regularly wear long-sleeved clothes, stay in the shade, and use sunscreen, respectively (Forsa & DAK Gesundheit, 2016;Engelhardt, 2016;G€ orig et al, 2018).…”
mentioning
confidence: 99%